Application of bioethylene in postharvest treatments - Gil, Rebeca; Campos-Martín, J. M.; Cervera-Chiner, Lourdes; Peinado, C.; Rojas-Argudo, Cristina; Salvador, Alejandra (2024)
Nowadays, most of the world's ethylene production comes from the petrochemical industry by steam cracking of naphtha. Nevertheless, steam cracking of hydrocarbons is one of the largest carbon dioxide (CO2) emitting processes in the chemicals industry. The production of bioethylene is a very interesting option as sustainable alternative with low CO2 emissions. Recently, through a European funded project (URBIOFIN), a demonstration scale preparation of high purity bioethylene has been obtained from the catalytic conversion of second-generation bioethanol from the organic fraction of municipal solid waste (OFMSW). Since ethylene is a gas commonly used in postharvest treatments, studies to validate the use of this bioethylene in these processes are needed. In this study was evaluated the application of bioethylene in banana ripening and citrus degreening treatments. The high purity bioethylene was diluted in nitrogen to 5 %. Two ripening trials were carried out on ‘Candevish’ bananas. After harvest, the fruit were subjected to a ripening treatment with bioethylene or commercial ethylene at 300 ppm for 24h at 17ºC. After the ripening process, the fruit were transferred at 17ºC for up 7 days. The evolution of color, firmness and total soluble solids after ripening treatment was similar when it was carried out with commercial ethylene or with bioethylene. Degreening treatments were performed on citrus (‘Iwasaki Satsuma’). Two homogeneous color groups of fruit were subjected to degreening treatment by application of bioethylene or commercial ethylene at 2 ppm, for 48 h at 20ºC. After degreening treatment, the fruit were transferred to 20ºC for 3 days. In both groups, no differences in external color, firmness, total soluble solids or acidity were found between treatments. According to the results obtained, bioethylene produced from OFMSW via bioethanol is shown to be a good alternative to the use of commercial ethylene in postharvest processes.